PDX models recapitulate the genetic and epigenetic landscape of pediatric T-cell leukemia - Richter-Pechańska, Paulina; Kunz, Joachim; Assenov, Yassen; Muckenthaler, Martina; Korbel, Jan Oliver; Kulozik, Andreas (EMBO molecular medicine, 2018)
Abstract We compared 24 primary pediatric T-cell acute lymphoblastic leukemias (T-ALL) collected at the time of initial diagnosis and relapse from 12 patients and 24 matched patient-derived xenografts (PDXs). DNA methylation profile was preserved in PDX mice in 97.5% of the promoters (? = 0.99). Similarly, the genome-wide chromatin accessibility (ATAC-Seq) was preserved remarkably well (? = 0.96). Interestingly, both the ATAC regions, which showed a significant decrease in accessibility in PDXs and the regions hypermethylated in PDXs, were associated with immune response, which might reflect the immune deficiency of the mice and potentially the incomplete interaction between murine cytokines and human receptors. The longitudinal approach of this study allowed an observation that samples collected from patients who developed a type 1 relapse (clonal mutations maintained at relapse) preserved their genomic composition; whereas in patients who developed a type 2 relapse (subset of clonal mutations lost at relapse), the preservation of the leukemia's composition was more variable. In sum, this study underlines the remarkable genomic stability, and for the first time documents the preservation of the epigenomic landscape in T-ALL-derived PDX models.